Kesiapsiagaan Tatanan Rumah Tangga Dalam Menghadapi Gempa dan Tsunami di Wilayah Zona Merah Kota Padang - Ade Ria Nofrianti; Sesmeri Haryani (Jurnal Ners, 2026)
Preparedness efforts aimed to reduce impacts from disasters. Padang City lies between Indo-Australian Plate meeting and Eurasian Plate wich vulnerable to earthquake and tsunami. 65% of population in Padang City live in red zone. This study aims to see household preparedness to face the earthquake and tsunami in the red zone area.This study uses combination method. Sampling data were done with multistage random sampling of 417 respondents, quantitative data were collected through questionnaires and qualitative data obtained by in-depth interview and focus group and discussion. Data were analyzed by univariate, bivariate (chi-square) and multivariate (logistic regression). The result of the research shows that there are correlation between knowledge, attitude, household policy, emergency response plan, disaster warning system, and resource mobilization, with the preparedness of the household order. Emergency response plans are the dominant variables associated with household preparedness. There are several obstacles in improving the preparedness of the household order to face the earthquake and tsunami. It is recommended that the government conduct training and simulation of disaster preparedness on a regular basis and improve the socialization of preparedness by utilizing information technology, preparing emergency response plan as household policy to face the earthquake and tsunami.